Genetic susceptibility to nicotine addiction: Advances and shortcomings in our understanding of the CHRNA5/A3/B4 gene cluster contribution. (15th October 2020) - Icick, Romain; Forget, Benoît; Cloëz-Tayarani, Isabelle; Pons, Stéphanie; Maskos, Uwe; Besson, Morgane
Abstract: Over the last decade, robust human genetic findings have been instrumental in elucidating the heritable basis of nicotine addiction (NA). They highlight coding and synonymous polymorphisms in a cluster on chromosome 15, encompassing the CHRNA5, CHRNA3 and CHRNB4 genes, coding for three subunits of the nicotinic acetylcholine receptor (nAChR). They have inspired an important number of preclinical studies, and will hopefully lead to the definition of novel drug targets for treating NA. Here, we review these candidate gene and genome-wide association studies (GWAS) and their direct implication in human brain function and NA-related phenotypes. We continue with a description of preclinical work in transgenic rodents that has led to a mechanistic understanding of several of the genetic hits. We also highlight important issues with regards to CHRNA3 and CHRNB4 where we are still lacking a dissection of their role in NA, including even in preclinical models. We further emphasize the use of human induced pluripotent stem cell-derived models for the analysis of synonymous and intronic variants on a human genomic background. Finally, we indicate potential avenues to further our understanding of the role of this human genetic variation. This article is part of the special issue on 'Contemporary Advances in Nicotine Neuropharmacology'. Highlights (85 characters including space each): CHRNA5/A4/B4 and nicotine addiction link relies on SNPs in high linkage disequilibrium. CHRNA5/A4/B4 cross-regulatory mechanisms should be considered in preclinical models . Refined neuropsychological assessment for addiction is needed in future studies.